2021
DOI: 10.9734/sajsse/2021/v10i130254
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Climate Factors in Job Creativity among Public University Librarians in Anambra State

Abstract: Education is the greatest stimulant for human development and the requisite for socio-economic advancement; the utility of libraries in education especially in tertiary institutions are as important as education itself. In third world countries like Nigeria, there is a great disparity in library utility. This study has therefore envisaged that unless librarians are creative given supportive climate, they may not actualize the potentials of libraries given funding inadequacies.  Thus, a survey study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It can cultivate innovative thinking, trigger work motivation, and improve the creativity of members (Shen et al, 2021). It plays a significant role in supporting and promoting the creative activities of individuals and organizations (Nwangwu et al, 2021) and also connects individual and organizational creativity (Chen & Li, 2010). A robust organizational innovation climate encourages mutual collaboration, information exchange, and interaction among members, in addition to providing adequate guidance for members to participate in organizational innovation (Aldabbas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It can cultivate innovative thinking, trigger work motivation, and improve the creativity of members (Shen et al, 2021). It plays a significant role in supporting and promoting the creative activities of individuals and organizations (Nwangwu et al, 2021) and also connects individual and organizational creativity (Chen & Li, 2010). A robust organizational innovation climate encourages mutual collaboration, information exchange, and interaction among members, in addition to providing adequate guidance for members to participate in organizational innovation (Aldabbas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…University education, irrespective of ownership (public or private), entrench a process by which those who are exposed to it, gender notwithstanding, are expected not to only develop intellectually (Alemu, 2018), but equally become worthy persons whose form of life as exhibited in the conduct of activities they are committed, are desirable (Okudo, 2012) and whose sense of judgment and thoughtfulness are commendable (Nwikpo, 2016). However, and quite unfortunately, research have shown that Nigerian university education is far from yielding the much-desired dividends (Nwangwu et al, 2021). This can be observed in the myriad of challenges that continues to plague the universities in the country, ranging from; corruption (Ezeh Indecent Dressing Among Female Undergraduates on Sexual Conduct and Study Engagement of Their Male Counterparts in Universities in the Southeast Nigeria & Etodike, 2016), social media-related crimes (Ezeonwumelu et al, 2021), cultism (Ajitoni & Olaniyan, 2018), persistent weapon-related violence (Nwikpo et al, 2021), educational backdrop (F.O.…”
Section: Introductionmentioning
confidence: 99%